2009
DOI: 10.30970/cma2.0107
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic investigation of reduction processes of gallium(III) complexes with some o,o'-dihydroxysubstituted azo dyes

Abstract: The voltammetric behaviour of Ga(III) complexes with o,o'-dihydroxysubstituted azo dyes (eriochrome red B (ERB), eriochrome black T (EBT), calcon (Calc), and kalces (Klc)) was investigated using cyclic linear-sweep voltammetry. Two new reduction peaks caused by reduction of the Ga(III)-azo dye complex compounds were registered on the voltammograms. The effect of pH, the concentration of azo dye and Ga(III) ions, and the sweep rate on the peak current was studied. The peak current changed linearly with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…108) The detection limit for a preconcentration time of 60 s was as low as 25 ng L −1 for gallium and 58 ng L −1 for germanium. Pysarevska et al 109) investigated the voltammetric behaviour of Ga(III) complexes with o,o'-dihydroxysubstituted azo dyes (eriochrome red B, eriochrome black T, calcon, and kalces) on a dropping mercury electrode using cyclic linear sweep voltammetry. The methods using Ga(III)azo dyes complexes were tested on the determination of gallium in intermetallic compounds of Zn-Ga, Sm-Ga, and in Gd 3 Sc 2 Ga 3 O luminophore.…”
Section: Adsorptive Cathodic Stripping Voltammetry Of Galliummentioning
confidence: 99%
“…108) The detection limit for a preconcentration time of 60 s was as low as 25 ng L −1 for gallium and 58 ng L −1 for germanium. Pysarevska et al 109) investigated the voltammetric behaviour of Ga(III) complexes with o,o'-dihydroxysubstituted azo dyes (eriochrome red B, eriochrome black T, calcon, and kalces) on a dropping mercury electrode using cyclic linear sweep voltammetry. The methods using Ga(III)azo dyes complexes were tested on the determination of gallium in intermetallic compounds of Zn-Ga, Sm-Ga, and in Gd 3 Sc 2 Ga 3 O luminophore.…”
Section: Adsorptive Cathodic Stripping Voltammetry Of Galliummentioning
confidence: 99%
“…The Ga(III) complexes formed with the investigated reagents show electrochemical activity. The complexes are reduced or oxidized according to the following main mechanisms: reduction of the elemental species in the adsorbed complex [7,[32][33][34], reduction of the ligand in the adsorbed complex [15,31,[35][36][37][38], or simultaneous reduction of the elemental species and the ligand in the adsorbed complex [39].…”
Section: Use Of Organic Agentsmentioning
confidence: 99%
“…Electrochemically active ligands are of special interest for the determination of Ga(III), which is not easily reduced in conventional supporting electrolytes. The peak corresponding to the reduction of the ligand in Ga(III) chelate is the basis of voltammetric techniques of Ga(III) determination with hydroxyazo dyes [15,31,[35][36][37][38], alizarin red S [40], and alizarin violet [39].…”
Section: Use Of Organic Agentsmentioning
confidence: 99%
“…However, linear sweep polarography is a selective and sensitive method for the determination of metals when electroactive complexing agents are used [5,6]. Particularly azo dyes have found successful utilization in polarographic methods [7][8][9]. Azo dyes contain an azo group, which is able to be reduced in the range of polarization of a mercury electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand in such complexes is reduced at different potentials. The difference between the reduction potentials of the complexes allows quantitative analysis of several metals without previous separation [7][8][9]. For instance, Poperechnaja et al [10] reported the possibility of simultaneous determination of In(III) and REE(III), but the authors only investigated optimal conditions of REE(III) determination.…”
Section: Introductionmentioning
confidence: 99%